2015
DOI: 10.4000/quaternaire.7172
|View full text |Cite
|
Sign up to set email alerts
|

Using stable isotopes of oxygen from tree-rings to study the origin of past flood events: first results from the iberian peninsula

Abstract: Using stable isotopes of oxygen from tree-rings to study the origin of past flood events: first results from the iberian peninsula Utilisation des isotopes stables de l'oxygène des cernes d'arbres pour déterminer l'origine des inondations passées : premiers résultats pour la péninsule ibérique

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 56 publications
1
10
0
2
Order By: Relevance
“…Indeed, several recent studies confirm that δ 18 O values can be a robust and reliable indicator of drought conditions and/or extreme hydroclimatic events [57,60,61]. We confirmed that δ 18 O values are tightly correlated with JJA precipitation sum over the substantial part of the Balkan Peninsula.…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, several recent studies confirm that δ 18 O values can be a robust and reliable indicator of drought conditions and/or extreme hydroclimatic events [57,60,61]. We confirmed that δ 18 O values are tightly correlated with JJA precipitation sum over the substantial part of the Balkan Peninsula.…”
Section: Discussionsupporting
confidence: 81%
“…Although this approach has not been widely tested in the tropics, López et al (2014) showed that floodplain trees in the Darien Gap, Colombia, produce more vessels when water levels rise, indicating that tree rings may retain useful information about past hydrology in these settings. Moreover, more detailed wood analyses based on both stable isotopes and chemistry elements are needed to corroborate hypotheses about the quality and characteristics of water flow condition during past flood regimens (Ferrio et al, 2015; Pop et al, 2014).…”
Section: Future Directionsmentioning
confidence: 99%
“…According to [30], when the EPS < 0.85, it means that the chronology is starting to be dominated by the individual signal of each tree series. However, the tree series can still be used for dendrochronology as long as it is not extremely low [31].…”
Section: The Chronologiesmentioning
confidence: 99%